Pengembangan Penilaian Autentik dalam Pembelajaran Sastra: Pendampingan bagi Guru Bahasa Indonesia SMP, SMA, dan SMK di Kota Pagaralam - Mulyadi Eko Purnomo; Nurhayati Nurhayati; A Saripudin; Armilia Sari (Jurnal Pengabdian Pada Masyarakat, 2020)
DEVELOPMENT OF AUTHENTIC ASSESSMENT DEVELOPMENT IN LITERATURE LEARNING: ASSISTANCE FOR INDONESIAN LANGUAGE TEACHERS IN SMP, SMA AND SMK IN PAGARALAM CITY. Evaluation is an important part of learning activities. Therefore, the Indonesian Language teacher must have sufficient competence regarding the implementation of the evaluation. In the 2013 Curriculum (K-13) there is one type of assessment that must be carried out, namely authentic assessment. The Indonesian language teachers must have sufficient ability about this, especially to assess the process and results of literature learning. Most of the Indonesian language teachers in Pagaralam City did not understand well about authentic assessment in literature learning. This is based on preliminary surveys conducted by the team as well as from letters given through Indonesian language teachers’ club (MGMP). Mentoring and guidance are conducted to them including workshops on developing authentic assessment rubriks and observation sheets. A total of 11 junior high schools, senior high school, and vocational school teachers in Pagaralam City participated in this activity. The method used was the delivery of information, discussion, and workshops. A test is conducted in the form of self-reflection about aspects of authentic assessment in literary learning at the beginning and end of the activity. The result showed that there is an increase in the ability of participants about authentic assessment in literature learning before and after the activity with an N-gain of 0.57, which means medium.